Is progression in the future liver remnant a contraindication for second-stage hepatectomy?. Issue 11 (November 2019) - Jouffret, Lionel; Ewald, Jacques; Marchese, Ugo; Garnier, Jonathan; Gilabert, Marine; Mokart, Djamel; Piana, Gilles; Delpero, Jean-Robert; Turrini, Olivier
Abstract: Background: Two-stage hepatectomy (TSH) strategy is used to treat patients with bilobar colorectal liver metastasis (CLM). However, many patients do not undergo the second hepatectomy owing to disease progression in the future liver remnant (FLR) after portal vein embolization (PVE). This study aimed to assess the impact of disease progression in the FLRs of patients who completed the first hepatectomy. Methods: 68 consecutive patients underwent the first hepatectomy followed by PVE. Six patients (9%) dropped out after the PVE (two-stage failed [TSF] group) because of unresectable hepatic or general disease progression. Seventeen patients (25%) completed their second hepatectomy despite disease progression in the FLR (new CLM [nCLM] group) as it was considered resectable, while 45 patients (66%) underwent the second hepatectomy (control group). Results: The 5-year overall survival rates in the TSF, nCLM, and control groups were 0%, 7%, and 60%, respectively ( P < 0.001). The median overall survival times between the TSF and nCLM groups were 26 months and 42 months ( P = 0.005). Patients in the nCLM group whose hepatic disease progression was detected preoperatively versus intraoperatively had comparable survival rates. Conclusion: Resectable hepatic disease progression in the FLR after PVE should not be considered a contraindication for the second hepatectomy.